Evaluasi Kualitas Sistem Riset Satya Wacana (RISAT) UKSW Berdasarkan Model ISO/IEC 25010 - Peku Jawang, Marindo; Johan J.C Tambotoh (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2026)
Riset Satya Wacana (RISAT) is an information system developed by Satya Wacana Christian University (UKSW) to support the management of research and community service activities. Although it has provided benefits, preliminary evaluations indicate various technical and functional issues experienced by users. Previous studies on system quality evaluation using the ISO/IEC 25010 standard generally focus only on specific characteristics and do not provide detailed technical recommendations, resulting in a gap in comprehensive evaluation and system improvement strategies. This study aims to evaluate the quality of RISAT based on the ISO/IEC 25010 standard within the Software Product Quality domain. This study employs a quantitative method, with data collected through questionnaires distributed to 70 active lecturers who use RISAT. The evaluation results show that the overall quality of RISAT is categorized as good, with an average score of 79%. Performance Efficiency (83%) and Security (82%) are categorized as very good, while other characteristics such as Functional Suitability (77%), Compatibility (78%), Usability (78%), Reliability (78%), Maintainability (76%), and Portability (77%) are categorized as good. This study contributes by providing a comprehensive evaluation covering the eight characteristics in the ISO/IEC 25010 Software Product Quality domain and identifying technical aspects that require improvement. The findings provide a basis for formulating more targeted improvement recommendations based on the evaluation results of each characteristic to enhance the quality of RISAT.